TAX BAILIFF ROLES POST ASSETS CONFISCATION ON SUSPECT OF TAX CRIME IN INDONESIA - Parluhutan Rajagukguk; Hariomurti Tri Kuntonegoro (Scientia Integritas Utama, 2022)
Empirical and juridical gaps in confiscating suspects' assets by tax investigators in Indonesia must be addressed immediately because they can potentially cause legal problems in the future. Two conclusions were produced based on the normative juridical method carried out through an inventory of primary, secondary, and tertiary legal materials. First, the confiscation of the suspect's assets in a criminal act in the taxation sector, as referred to in Article 44 paragraph (2) letter j of the KUP Law, still leaves a legal vacuum and, at the same time, ignores the checks and balances mechanism in the assessment, maintenance, management, and or auction after the tax investigators carry out the confiscation of assets. Second, the role of the tax bailiff after the confiscation of the suspect's assets carried out by tax investigators is more reflective of justice, legal certainty, and public benefits for the actors involved in confiscating and recovering losses in the state revenue. It is recommended to reform the Tax Collection Law in terms of adding the authority of the tax bailiff in Indonesia as well as the making of a Government Regulation or at least a Regulation of the Minister of Finance which regulates the number of legal vacancies after the confiscation of the suspect's assets is carried out by tax investigators.